Acute hyperglycemia suppresses left ventricular diastolic function and inhibits autophagic flux in mice under prohypertrophic stimulation. Issue 1 (December 2016) - Xie, Jiahe; Cui, Kai; Hao, Huixin; Zhang, Yingxue; Lin, Hairuo; Chen, Zhenhuan; Huang, Xiaobo; Cao, Shiping; Liao, Wangjun; Bin, Jianping; Kitakaze, Masafumi; Liao, Yulin
Abstract Background Left ventricular (LV) dysfunction is closely associated with LV hypertrophy or diabetes, as well as insufficient autophagic flux. Acute or chronic hyperglycemia is a prognostic factor for patients with myocardial infarction. However, the effect of acute hyperglycemia on LV dysfunction of the hypertrophic heart and the mechanisms involved are still unclear. This study aimed to confirm our hypothesis that either acute or chronic hyperglycemia suppresses LV diastolic function and autophagic flux. Methods The transverse aortic constriction (TAC) model and streptozocin-induced type 1 diabetic mellitus mice were used. LV function was evaluated with a Millar catheter. Autophagic levels and autophagic flux in the whole heart and cultured neonatal rat cardiomyocytes in response to hyperglycemia were examined by using western blotting of LC3B-II and P62. We also examined the effect of an autophagic inhibitor on LC3B-II and P62 protein expression and LC3 puncta. Results In mice with TAC, we detected diastolic dysfunction as early as 30 min after TAC. This dysfunction was indicated by a greater LV end-diastolic pressure and the exponential time constant of LV relaxation, as well as a smaller maximum descending rate of LV pressure in comparison with sham group. Similar results were also obtained in mice with TAC for 2 weeks, in addition to increased insulin resistance. Acute hyperglycemic stress suppressed diastolic function in mice with myocardial hypertrophy, as evaluated by invasive LV hemodynamic monitoring. Mice with chronic hyperglycemia induced by streptozocin showed myocardial fibrosis and diastolic dysfunction. In high glucose-treated cardiomyocytes and streptozocin-treated mice, peroxisome proliferator-activated receptor-γ coactivator 1α was downregulated, while P62 was upregulated. Autophagic flux was also significantly inhibited in response to high glucose exposure in angiotensin-II treated cardiomyocytes. Conclusions Acute hyperglycemia suppresses diastolic function, damages mitochondrial energy signaling, and inhibits autophagic flux in prohypertrophic factor-stimulated cardiomyocytes.